Simulasi Daya Harmonik berbasis Transformasi Wavelet dengan Matlab - Ulul Ilmi; zainal abidin (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2019)
The progress of power electronics application technology, harmonic pollution in the electrical power system network is increasing seriously, having a serious impact on the energy supply network and equipment. In this discussion, the author studied harmonic characteristics, analysis of harmonic detection methods using wavelet algorithms with Matlab. The results of the simulation show that wavelet transforms can compose harmonic components that are settled in the system according to their needs.